Effect of TIJEK Nuggets as a Local Supplementary Food on Weight Gain among Stunted Toddlers: A Pre-Experimental Study - Erlina Nasution; Fitriyani Pulungan; Ida Nurhayati; Syahira Addina; Elisa Julianti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Stunting remains a critical public health challenge in Indonesia, particularly in regions like Deli Serdang Regency, North Sumatra, where prevalence rates remain elevated despite ongoing interventions. This pre-experimental one-group pretest-posttest study evaluated the effect of TIJEK Nuggets a locally developed supplementary food made from tempeh (fermented soybeans), anchovies, chicken eggs, and spices as a nutrition intervention to improve the nutritional status of stunted toddlers aged 2-5 years in Pantai Labu Pekan Village. From a population of 45 eligible toddlers, 30 participants meeting the inclusion criteria (willingness to participate and measurable anthropometrics) were consecutively sampled. Baseline height and weight measurements served as pretest values, followed by daily administration of 100 grams of TIJEK Nuggets (divided into two servings) for 14 days, with posttest anthropometrics recorded thereafter. Nutritional analysis confirmed that 100 grams (4 pieces) of TIJEK Nuggets provided 150.61 kcal of energy, 26.83 g of carbohydrates, 7.92 g of protein, 11.61 g of fat, 62.56 g of water, and 1.40 g of ash, leveraging high-protein local ingredients to address macronutrient deficiencies common in stunting. Results showed no significant change in mean height (pretest-posttest: 92.72 cm ± 7.69 cm), but averages were identical due to minimal linear growth over the short term. However, mean weight increased significantly from 12.77 kg ± 2.03 kg to 13.39 kg ± 2.04 kg (p=0.001), indicating TIJEK Nuggets effectively promoted short-term weight gain. This aligns with biological expectations: height reflects chronic malnutrition, which responds to prolonged interventions, while weight responds more rapidly to energy-dense supplements. In conclusion, TIJEK Nuggets demonstrate promise as an accessible, effective supplementary food for short-term weight improvement in stunted toddlers, warranting broader, controlled applications within multifaceted anti-stunting strategies Keywords: Stunting, Toddlers, Nutritional Status, TIJEK Nuggets, Local Food